A Bronze Statue of a Strigil Cleaner Found Underwater at the Islet of Vele Orjule near Lošinj (Archaeologia Adriatica, 2007)
This article discusses the bronze statue of a young athlete of more than lifesize proportions found underwater by the small island of Vele Orjule near Lošinj. This article has already been published in the catalogue of the exhibition in Florence in Italian and English. As it has not been published yet in Croatia, the author considered that the results should also be presented to the Croatian scholarly and broader public. The statue is a Hellenistic copy depicting an athlete cleaning his scraper or strigil after competition (most probably wrestling) of an original from the period of around 350 BC. Such a conclusion was reached after analysis of the sculpture, and particularly the head and hairstyle, which can be compared to several portraits from the above period. It is most likely that the sculpture from Orjule also represents a portrait of a certain individual (of unknown name, of course), who served as a model. The statue was sunk, most probably thrown from a boat during a storm, on its way to an unknown destination. Many harbours are possible, but the most probable would be the wealthy villa in Verige Bay on the island of Veli Brijun.
Keywords: bronze statue; Vele Orjule